2012
DOI: 10.1103/physreve.85.021407
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of the branch structure of diffusion-limited aggregates

Abstract: We examine the branch structure of radial diffusion-limited aggregation (DLA) clusters for evidence of multifractality. The lacunarity of DLA clusters is measured and the generalized dimensions D(q) of their mass distribution is estimated using the sandbox method. We find that the global n-fold symmetry of the aggregates can induce anomalous scaling behavior into these measurements. However, negating the effects of this symmetry, standard scaling is recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The crucial impact of the lattice anisotropy on the DLA growth naturally disappears for the intrinsically isotropic off-lattice DLA that had also been extensively investigated (see [38][39][40][41][42][43][44] and references therein). This rises an important question: how to explain the qualitative difference between the on-lattice and off-lattice DLA?…”
Section: Discussionmentioning
confidence: 99%
“…The crucial impact of the lattice anisotropy on the DLA growth naturally disappears for the intrinsically isotropic off-lattice DLA that had also been extensively investigated (see [38][39][40][41][42][43][44] and references therein). This rises an important question: how to explain the qualitative difference between the on-lattice and off-lattice DLA?…”
Section: Discussionmentioning
confidence: 99%
“…We chose regular constructions because they can be associated with the mean DLA branching number 5, resulting in synthetic clusters that look somewhat similar to DLA clusters. curves obtained for mono and multifractal toy DLA synthetics In order to put our results in perspective, Figure 10 shows our obtained multifractal obtained in [32] and [33] for DLA clusters with similar mass. All three results are for DLA clusters of 1 million particles.…”
Section: -Application To the Diffusion-limited Aggregation (Dla) Promentioning
confidence: 99%
“…All three results are for DLA clusters of 1 million particles. In contrast to [32] random pivot points, [33] uses 5*10 4 random pivot points and square boxes for size sandbox method. Also, the R interval for this study was wider we conducted the following test: we (log(6)/log(3)) and confirmed that the sample sizes we created a synthetic multifractal having a D q…”
Section: -Application To the Diffusion-limited Aggregation (Dla) Promentioning
confidence: 99%
“…T hese syst ems include diff usion limit ed aggregat ion [3][4][5], fluid flow t hrough random porous media [6], at omic spect ra of rare-eart h element s [7], clust erclust er aggregat ion [8] and t urbulent flow [9]. In physiology, mult ifract al st ruct ures have been found in heart rat e variability [10] and brain dynamics [11], and mult ifract al analysis has been helpful in dist inguishing between healthy and pathological patients [12].…”
Section: Introductionmentioning
confidence: 99%